Tuning the surface immunomodulatory functions of polyetheretherketone for enhanced osseointegration. (February 2020) - Gao, Ang; Liao, Qing; Xie, Lingxia; Wang, Guomin; Zhang, Wei; Wu, Yuzheng; Li, Penghui; Guan, Min; Pan, Haobo; Tong, Liping; Chu, Paul K.; Wang, Huaiyu
Abstract: The adverse macrophage-mediated immune response elicited by the surface of polyetheretherketone (PEEK) is responsible for the formation of ﬁbrous encapsulation and resulting inferior osseointegration of PEEK implants in the dental and orthopedic fields. Therefore, endowing the PEEK surface with immunomodulatory ability is an appealing strategy to enhance implant-bone integration. Herein, a reliable and cost-effective method to construct adherent films with tunable nanoporous structures on PEEK is described. The functionalized surface not only suppresses the acute inflammatory response of macrophages, but also provides a favorable milieu for osteogenic differentiation of human bone marrow mesenchymal stem cells (hBMSCs). Whole genome expression analysis reveals that the suppression effect arises from synergistic inhibition of focal adhesion, Toll-like receptor, and NOD-like receptor signaling pathways, as well as the attenuating loop through the JAK-STAT and TNF signaling pathways in macrophages. Further in vivo studies confirm that the functionalized surface induces less fibrous capsule formation and an improved bone regeneration. The nanoporous films fabricated on PEEK harmonize the early macrophage-mediated inflammatory response and subsequent hBMSCs-centered osteogenic functions consequently yielding superior osseointegration.